1999
DOI: 10.1002/(sici)1099-1263(199912)19:1+<s19::aid-jat608>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Buforin I, a natural peptide, inhibits botulinum neurotoxin B activity in vitro

Abstract: Botulinum neurotoxin B (BoNT/B) serotype specifically cleaves between the amino acids glutamine and phenylalanine (Q and F bond) in position 76–77 of synaptobrevin (VAMP2). We evaluated peptides that contain the QF cleavage site but are not identical in primary structure to the VAMP2 sequence surrounding the QF site for both inhibition of BoNT/B proteolytic activity and as substrates for BoNT/B. A reverse‐phase high‐performance liquid chromatography (RP‐HPLC) method was used to measure digested peptides. A dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…However, two non-peptidic inhibitors have been described 46,47 (TABLE 6). With regard to pseudopeptides, phosphoramidon and three of its synthetic derivatives were found to be weak inhibitors 48 , whereas buforin I has also shown activity against the BoNT/B LC 49 . Recently, a Cys-containing peptide inhibitor was also reported 50 .…”
Section: Staphylococcal Human Avianmentioning
confidence: 99%
“…However, two non-peptidic inhibitors have been described 46,47 (TABLE 6). With regard to pseudopeptides, phosphoramidon and three of its synthetic derivatives were found to be weak inhibitors 48 , whereas buforin I has also shown activity against the BoNT/B LC 49 . Recently, a Cys-containing peptide inhibitor was also reported 50 .…”
Section: Staphylococcal Human Avianmentioning
confidence: 99%
“…Because of availability of reagents, research has mostly been focused on finding inhibitors of the protease activity. As a result, peptide inhibitors (Schmidt et al 1998;Garcia et al 1999;Schmidt & Stafford 2002) and small molecule inhibitors (Burnett et al 2003) of type A and B light chain proteolytic activities have been reported.…”
mentioning
confidence: 99%
“…On the other hand, cecropin A had the highest affinity for labeled toxoid E; its K d (10 -10 M) was at least ten-fold lower than all others measured and was due to both significantly higher k on and lower k off rates when compared to other AMPs and the other toxins (P < 0.01). These K d s were significantly lower than the IC 50 s measured for buforin-II and botulinum toxin B in inhibition assays [ 24 , 25 ], as well as the inhibition or Michaelis constants of other peptide substrate analogs and inhibitors of botulinum neurotoxins [ 36 - 40 ]. However, a number of peptide inhibitors with nanomolar dissociation constants have recently been developed [ 41 ].…”
Section: Resultsmentioning
confidence: 97%
“…It is widely held that the natural mechanistic targets for the microbiocidal activity of many AMPs are cellular membranous structures; a large body of work describes the theory and practical aspects of AMP-membrane interactions [ 19 - 23 ]. It was therefore surprising when Garcia and colleagues found that the AMP buforin-I ( Table 1 ) inhibited the protease activity of botulinum neurotoxin B in solution [ 24 ]. In large part because of Garcia's original observations and subsequent work [ 25 , 26 ], we attempted to assess the potential of a number of other AMPs unrelated to buforins to detect inactivated botulinum toxins A, B, and E in rapid assays.…”
Section: Resultsmentioning
confidence: 99%